2011
DOI: 10.20538/1682-0363-2011-1-48-54
|View full text |Cite
|
Sign up to set email alerts
|

T-regulatory cells subpopulation in bronchial asthma and heterogeneous phenotypes of chronic obstructive pulmonary disease

Abstract: Aim of the study was to investigate the levels of individual subpopulations of T-regulatory (T-reg) cells in patients with different phenotypes of chronic obstructive pulmonary disease (COPD) with moderate bronchial asthma and healthy volunteers. COPD was associated with increased level of natural (CD4+CD25high) T-cells, while emphysematous phenotype of disease was associated with the highest pool of natural CD4+CD25high. Bronchial asthma was associated with low levels of inducible (CD4+ FoxP3+ ) T-reg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The findings of the study are coherent with the reported information that chronic inflammatory process during bronchial asthma is accompanied with intensification of synthesis of biologically active substances which have an effect on the lymphocytes' receptor system, resulting in change of the level of their functional capacities [9,13].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of the study are coherent with the reported information that chronic inflammatory process during bronchial asthma is accompanied with intensification of synthesis of biologically active substances which have an effect on the lymphocytes' receptor system, resulting in change of the level of their functional capacities [9,13].…”
Section: Resultssupporting
confidence: 88%
“…One of mechanisms of BA pathogenesis is imbalance of cytokines of various T-helper profiles, in particular, IFNγ and IL-4, which characterize the immune response polarization of Th1 and Th2 inflammation type [2,7]. IFNγ regulates the differentiation of naïve CD4 + -cells into Th1 and inhibits the proliferation of Th2 [7,9]. Average levels of spontaneous production of IFNγ and IL-4 in children with allergen-induced phenotype were equal to 8.07±1.42 pg/ml and 5.04±0.08 pg/ml, after mitogen induction -to 16.38±1.77 pg/ml and 13.15±1.21 pg/ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variety of clinical symptoms of these diseases the development of inflammation is largely determined by immune system [ 3 – 6 ]. It is known that eosinophilic inflammation in asthma is controlled by CD4 + lymphocytes [ 7 , 8 ]. The disorders of respiratory function are occasional and reversible.…”
Section: Introductionmentioning
confidence: 99%
“…In COPD inflammation involves neutrophils, macrophages, and CD8 + lymphocytes. An important feature of COPD is a progressing pulmonary obstruction concurrent with airway remodeling [ 8 , 9 ]. Despite the differences in the development mechanisms of asthma and COPD, these diseases have some common features in clinical manifestations and prevention and treatment strategies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%